ADMINISTRATIVE RESPONSIBILITY AS ONE TYPE OF LEGAL LIABILITY - Matvejevs, Aleksandrs (Administrative and Criminal Justice, 2019)
Currently, the issue of administrative responsibility seems to be very relevant and requiring additional scientific research, since the norms of administrative responsibility systematically undergo a number of changes. And this is right, because the changes in the regulations of administrative responsibility should consist of an analysis of legal relations’ dynamics at the present stage due to the fact that the legislation on administrative responsibility as one of the types of legal responsibility requires a unified approach to develop a clear scientific concept and improve it.